An Analysis of Quran Study Implementation at Secondary School in Padang Panjang City West Sumatera - Zamzami, Zamzami (Khalifa Journal of Islamic Education, 2021)
This study aims to analyze how the process, implementation and results of learning the Qur’an in Junior High Schools in Padang Panjang City, West Sumatra Province, Indonesia. This study uses a qualitative method with a case study approach, data sources are taken through direct observation of the object of research and in-depth interviews with school principals, teachers and students. All data were then analyzed thematically with techniques of collection, reduction, data analysis and closed with research conclusions. Overall the results of the study found that; First, the study planning has gone well, because administratively the school has fully prepared all the learning preparations such as teachers, curriculum, lesson plans, media and other aspects of learning support. Second, the process of implementing Qur'anic learning has also been going well, because all teachers carry out professionally their duties and responsibilities related to what has been planned and agreed upon so that the desired goals are achieved. Third, further evaluation of learning has shown good results, evaluation of learning the Qur’an is assessed based on three aspects of learning outcomes, namely aspects of knowledge, attitudes and skills of students related to knowledge and ability to read the Qur’an. The results of the study show that the seriousness of all school elements is the most important part of the success of a program, in fact it can be an example and reference for other schools related to the Qur'an learning program.